Targeting Hepatitis B Virus With CRISPR/Cas9 - Christoph Seeger; Ji A Sohn (Elsevier, 2014)
Hepatitis B virus persistence in infected hepatocytes is due to the presence of covalently closed circular DNA (cccDNA), the template for the transcription of viral RNAs. Antiviral therapies with nucleoside analogues inhibit replication of HBV DNA in capsids present in the cytoplasm of infected cells, but do not reduce or destroy nuclear cccDNA. To investigate whether cccDNA derived from infectious HBV could be directly targeted for destruction, we used the CRISPR/Cas9 system in HepG2 cells expressing the HBV receptor sodium taurocholate cotransporting polypeptide (NTCP). We tested different HBV-specific guide RNAs and demonstrated that they could inhibit HBV infections up to eightfold. Inhibition was due to mutations and deletions in cccDNA similar to those observed with chromosomal DNA cleaved by Cas9 and repaired by nonhomologous end joining (NHEJ). Interferon alpha (IFN-α) did not have a measurable effect on the antiviral activity of the CRISPR/Cas9 system, suggesting that Cas9 and NHEJ activities are not affected by induction of an innate immune response with the cytokine. Taken together, our results demonstrated that Cas9 can be recruited to cccDNA, opening the possibility for the development of future antiviral strategies aimed at targeting cccDNA for endonucleolytic cleavage with small molecules.